2019
DOI: 10.1111/tct.12992
|View full text |Cite
|
Sign up to set email alerts
|

Current hand hygiene education is suboptimal

Abstract: SUMMARY Background To address the low levels of hand hygiene compliance (HHC) at our academic medical centre, we developed an annual patient safety course required for all incoming third‐year medical students. Based on previous observations of medical students, it was determined that hand hygiene (HH) would be a central component of the course. Methods Over a 1‐year period (2015/16), we observed third‐ and fourth‐year medical students who had participated in the annual patient safety course entering three inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…In this study, men and women presented various reasons why they did not comply with HH: men pointed to setbacks in performing HH, i.e. lack of time, lack of role models, and unclear requirements, while women pointed to dry or cracked skin and forgetfulness [22].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In this study, men and women presented various reasons why they did not comply with HH: men pointed to setbacks in performing HH, i.e. lack of time, lack of role models, and unclear requirements, while women pointed to dry or cracked skin and forgetfulness [22].…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, in a study by Wałaszek [12], the average age of the respondents and higher education were associated with greater knowledge of hand hygiene. A study by Birnbach [22] carried out an observation of 150 medical students (third and fourth year of study) who, after undergoing HH training, completed internships in the intensive care unit; in this study 75% of men and 25% of women did not perform HH in the required situations. This study showed that even if medical students received intensive HH education, compliance remained low [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…W e read with interest the article by Birnbach et al regarding the poor hand hygiene compliance (HHC) of medical students despite a 5-day course. 1 As fifth-year medical students at Imperial College London, we propose improving HHC amongst medical students through quality improvement projects (QIPs).…”
mentioning
confidence: 99%
“…4 In our opinion, students fail at HHC because of a lack of exposure to the complications and severity of poor HHC, namely hospital-acquired infections. 1 By undertaking projects, students can experience first-hand the importance of HHC, and identify reasons for failure as they improve their own compliance. 3 As HHC is a theme applicable to most areas of care, groups can be further challenged to relate their QIP to a chosen specialty, to enhance student engagement and indicate relevance.…”
mentioning
confidence: 99%